Controlled burn on Pawnee National Grassland - Kaplan, Nicole, photographer (Colorado State University. Libraries, 2002)
Controlled burning on Pawnee National Grassland was implemented to create habitat for the mountain plover.
Keywords: SGS; vegetation; burn